Socialism: Utilitarian and deontic - Skempton, Simon (2023)
This article argues that those who advocate the capitalist market system on the basis of the ‘invisible hand’ or ‘spontaneous order’ belong to a tradition in political philosophy which attempts to find ways to get the most out of a flawed human nature, whereas socialists tend to belong to the opposing tradition which maintains faith in human improvement. The former tradition involves a kind of consequentialism in which goodness can be achieved irrespective of people’s intentions, whereas the latter tradition, with its emphasis on conscious decision making and the ‘good will’, includes Kantian deontology. Both utilitarian and deontological arguments for socialism are discussed, but it is argued that the emphases on human dignity and on deliberate planned action make socialist arguments sit more comfortably with deontology. This is most clearly the case when socialist thinkers transform Kantian monological universality into dialogical and communicative mutuality.